THEORETICAL PREREQUISITES AND PERSPECTIVES FOR THE STUDY OF PHRASEOLOGICAL UNITS IN UZBEK LINGUISTICS - Sheralieva Shirin Abdisalomovna; Sultonova Shoxista Muxammadjanovna (Journals Park Publishing, 2024)
This article discusses the theoretical prerequisites and perspectives for the study of phraseological units in Uzbek linguistics. Several works of scientists on this subject have been investigated and different views of the concept (by scientists) were shown as examples. Besides that, the topicality of the work is conditioned by the profound interest of language specialists in the linguistic peculiarities of set expressions.
Keywords: phraseology, phrase, phraseological unit, PU, word combination, meaning, linguistics.